1995
DOI: 10.1002/masy.19950980134
|View full text |Cite
|
Sign up to set email alerts
|

New materials with novel topologies. Synthesis and characterisation of telomers and polymers with ribbon topology

Abstract: The five, seven and nine ring analogues of thianthrene have been made as model compounds for ribbon polymers based on the structural motif shown below. The smaller molecules are soluble and readily characterised but the nine ring model compound and polymers based on this structural motif are insoluble and intractable. Analogues of the model compounds and polymers which carry decyl substituents are soluble upto species having about seventy rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[1][2][3] In particular their thermal and chemical stability is much higher, as the breaking of at least two bonds is necessary for scission of a polymer. Ladder compounds, especially of the p-conjugated type, are also important in the field of organic electronic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In particular their thermal and chemical stability is much higher, as the breaking of at least two bonds is necessary for scission of a polymer. Ladder compounds, especially of the p-conjugated type, are also important in the field of organic electronic materials.…”
Section: Introductionmentioning
confidence: 99%
“…In 1995 Feast et al reported on a novel synthetic approach towards PDT in a "synchronous" A 4 B 4 -polycondensation fashion. [2] This technique should have allowed the formation of both strands in one step. However, the resulting polymer contained large amounts of non-reducible sulfone groups and other defects.…”
Section: Introductionmentioning
confidence: 99%